Inherited or Earned? : Performance of Foreign Banks in Central and Eastern Europe - Jurzyk, Emilia (IMF Working Papers; Working Paper ;, 2010)
Using a combination of propensity score matching and difference-in-difference techniques we investigate the impact of foreign bank ownership on the performance and market power of acquired banks operating in Central and Eastern Europe. This approach allows us to control for selection bias as larger but less profitable banks were more likely to be acquired by foreign investors. We show that during three years after the takeover, banks have become more profitable due to cost minimization and better risk management. They have additionally gained market share, because they passed their lower cost of funds to borrowers in terms of lower lending rates. Previous studies failed to pick up the improvements in performance of takeover banks, because they did not account for the performance of financial institutions before acquisitions.